2019
DOI: 10.1001/jamainternmed.2019.0677
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic Drug Exposure and the Risk of Dementia

Abstract: Key Points Question Is the risk of dementia among persons 55 years or older associated with the use of different types of anticholinergic medication? Findings In this nested case-control study of 58 769 patients with a diagnosis of dementia and 225 574 matched controls, there were statistically significant associations of dementia risk with exposure to anticholinergic antidepressants, antiparkinson drugs, antipsychotic drugs, bladder antimuscarinics, and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

24
398
5
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 477 publications
(435 citation statements)
references
References 45 publications
24
398
5
8
Order By: Relevance
“…However, the association of dementia risk with diabetes mellitus found in previous studies was not evident among the top predictive features [30]. Anticholinergic drug exposure has also been identified as a risk factor for dementia [31]. Anticholinergic drugs figured prominently in the list of top predictive features in our models as well (Supplementary Material D).…”
Section: Discussionmentioning
confidence: 70%
“…However, the association of dementia risk with diabetes mellitus found in previous studies was not evident among the top predictive features [30]. Anticholinergic drug exposure has also been identified as a risk factor for dementia [31]. Anticholinergic drugs figured prominently in the list of top predictive features in our models as well (Supplementary Material D).…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, a recent study demonstrated that PD patients with a high cumulative dose of anticholinergics had an increased risk of being diagnosed with dementia . In addition, a recently published case‐control study demonstrated in a cohort of elderly patients that exposure to several types of strong anticholinergic drugs was associated with an increased risk of dementia . This further suggests that providers should be cautious about anticholinergic drug usage in the PD patient population.…”
Section: Discussionmentioning
confidence: 99%
“…11 In addition, a recently published case-control study demonstrated in a cohort of elderly patients that exposure to several types of strong anticholinergic drugs was associated with an increased risk of dementia. 13 This further suggests that providers should be cautious about anticholinergic drug usage in the PD patient population. Overall, levodopa prescribing did not change significantly from 2010 to 2017.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations